Bligh master mariner - Mundle, Robert (Pen & Sword Maritime, 2012)
The Eighteenth Century was an era when brave mariners took their ships beyond the horizon in search of an unknown world. Those chosen to lead these expeditions were exceptional navigators, men who had shown brilliance as they ascended the ranks in the Royal Navy. They were also bloody good sailors.